Features of upper ocean and surface waves during the passage of super typhoon Hinnamnor (2022) - Zhang, Ting (Frontiers in Marine Science, 2023)
Scientific understanding of super typhoons (STYs) is essential for environmental and human-made disaster prevention. The interactive processes among the atmosphere, ocean, and surface waves have an intimate relationship within the STY system. This study chose STY Hinnamnor (2022) as an example and used multi-source data to investigate how it affected the upper ocean. First, Argo floats data at two positions were collected to investigate the variation of sea surface temperature (SST), sea surface salinity (SSS), isothermal layer depth (ILD), mixed layer depth (MLD), barrier layer thickness (BLT), and eddy viscosity (EV) during pre- and post-STY. The STY passed through two Argo floats; hence, the SST, ILD, and BLT significantly decreased post-STY, whereas the MLD and EV increased. The SSS decreased by 0.26 psu where the STY passed southwestward, whereas it increased by 0.11 psu where the STY began to move northward. Subsequently, the remote sensing data and re-analysis data were used to study the evolution of the SST, precipitation, runoff, and profiles of the upper ocean pre- and post-STY. The results reveal that intensive vertical mixing and upwelling occurred in the region where the direction of the STY movement switched. It also revealed that the runoff and heavy precipitation increased the water salinity in this area. In addition, the reanalysis data indicated that the significant wave height (SWH) and the mean wave period (MWP) near the cyclone center became longer than in other areas. The temporal evolution of the spectral peak period (SPP) demonstrated the generation of a swell zone on the right side of the typhoon track when the STY moved northward.